Simulating the Impact of Defective Rates on the Bullwhip Effect in a Supply Chain: A Reciprocating Compressor Manufacturing Case Study with Exponential Smoothing Forecasting - Pradthana Rattanapuchong; Natanaree Sooksaksun; Kittiwat Sirikasemsuk (My University, 2024)
This study was dedicated to simulating the impact of defective rates on the bullwhip effect within the context of a supply chain, with a specific focus on a case study involving reciprocating compressor manufacturing. The supply chain configuration encompassed a distributor, a factory, customer, and a remanufacturer. Customer demand was forecasted utilizing the exponential smoothing method, while an order-up-to inventory policy was implemented. The results unveiled a direct correlation between an increase in defective rates and a heightened bullwhip effect. Moreover, the study demonstrated that an elevation in the average yield rate corresponded to a mitigation of the bullwhip effect.
Keywords: Management and Optimization Techniques